PKM pelatihan model manajemen edu–finance UMKM konveksi di Kota Makassar - Anwar Ramli; Nurhaedah Nurhaedah (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Training can provide tangible changes for UMKM Konveksi to grow, expand and develop abilities specifically inmanaging their management financial independently and even able to increase profitability. Problems to help UMKM Konveksiin this training study, analyze and implement the implementation of management financial with an management edu-financemodel for UMKM Konveksi in Makassar. The indicators used as benchmarks for evaluating / implementing the training areactivities: 1) The ability of participants to understand the material provided, 2) The ability of participants to manage data andanalyze so that it becomes useful information, and 3) Discipline, participation, enthusiasm, and motivation of participants duringthe training. The training can be utilized directly by UMKM Konveksi, including: 1) The benefits that can be felt by theparticipants for the material presented either in the form of theoretical, simulation and independently adapted practices based ontheir tasks that will support their work with the fashion management edu- finance; 2) The ability of participants in practicing howto use activities, activities in the provision of funds, and managing assets that have been applied, as well as UMKM Konveksiperform practices on how to make simple financial statements that will be practiced directly in the business so that UMKMKonveksi can maximizing the profit that can be obtained, and 3) UMKM Konveksi Participants are very disciplined,participating, enthusiastic, and motivated during the training.